Safety and Efficacy of Mesenchymal Stem Cells in Burn Therapy: Systematic Review - Theresia Dini; Yudhi Nugraha; Rika Revina; Karina Karina (Molecular and Cellular Biomedical Sciences, 2022)
The experimental research on the use of mesenchymal stem cells (MSCs) for burn therapy has been published several times. However, current clinical procedure remains a challenging discussion. This systematic review assesses the safety and efficacy of administering mesenchymal stem cells (MSCs) to burns and determines the most effective source of MSCs for burn therapy. We reviewed several studies through PubMed, Google Scholar, Science Direct, and DOAJ online databases. PRISMA-P 2020 method was used based on inclusion and exclusion criteria that were re-selected through Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results from 13 articles showed that MSCs are safe for burn therapy with minimal side effects/complications and have the potential to repair tissue and accelerate burn healing through several mechanisms. The treatment of MSCs in burns is influenced by donor characteristics and related to the severity and area of the burn. It can be concluded that the administration of MSCs is safe and effective in burn therapy. Keywords: burns, mesenchymal stem cells, therapeutic safety, therapeutic efficacy, wound healing